Copying Life: Synthesis of an Enzymatically Active Mirror-Image DNA-Ligase Made of D-Amino Acids. Issue 5 (16th May 2019) - Weidmann, Joachim; Schnölzer, Martina; Dawson, Philip E.; Hoheisel, Jörg D.
Summary: Our objective is the creation of a mirror-image synthetic biology: that is, to mimic, entirely independent of Nature, a biological system and to re-create it from artificial component parts. Utilizing enantiomeric L-nucleotides and D-amino acids rather than the natural components, we use chemical synthesis toward a basic, self-replicating mirror-image biological system. Here, we report the synthesis of a functional DNA-ligase in the D-enantiomeric conformation, which is an exact mirror-image of the natural enzyme, exhibiting DNA ligation activity on chirally inverted nucleic acids in L-conformation, but not acting on natural substrates and with natural co-factors. Starting from the known structure of the Paramecium bursaria chlorella virus 1 DNA-ligase and the homologous but shorter DNA-ligase of Haemophilus influenza, we designed and synthesized chemically peptides,  which could then be assembled into a full-length molecule yielding a functional protein. The structure and the activity of the mirror-image ligase were characterized, documenting its enantiospecific functionality. Graphical Abstract: Highlights: Our objective is the creation of an enantiomeric, self-replicating molecular system Toward this end, a DNA-ligase in D-enantiomeric protein conformation was synthesized This mirror-image to the natural enzyme exhibits activity on chirally inverted DNA Abstract : Weidmann et al. report about the synthesis of an enantiomeric DNA-ligase. It represents an important addition to the enzyme repertoire needed for setting up a self-replicating molecular system that is independent from Nature but identical in terms of biophysical and biochemical parameters.